Peningkatan Self Compassion Untuk Mereduksi Perilaku Adiktif Pengguna Sosial Media Bagi Siswa SMP - Agus Rizal; Budi Purwoko; Retno Tri Hariastuti (Indonesian Journal of Learning Education and Counseling, 2020)
The research aims to describe the process of counseling services on improving self-compassion of students in Surabaya Private Junior High Schools who have problems with addictive behaviors using sophisticated technology especially the social media section. The research methodology uses a descriptive qualitative method by collaborating with library research with an open questionnaire process and interviews with junior high school students who often use social media and addictive behavior on social media. The results of the study indicate that efforts to increase student self-compassion are able to show reduction and decrease the social media addictive behavior of students. Because in the counseling process increasing self-compassion requires a long process and factors that influence the addictive behavior of social media users. As well as looking at student activities from school and the environment so as not to influence about negative actions.